Transparansi dalam Sistem Pencalonan Pemilihan Walikota Kupang Tahun 2017 (Jurnal Kajian Media, 2018)
Transparency in general election and/or the election of governor, regent, and mayor, was one of the principal election. The party which was demanded to always do this principle was the organizer. Transparency in the production and implementation of the rules and transparency was about the budgeting etc. In the certain context, transparency was required in a system. Transparency in the mayor and vice election of Kupang in 2017 was the research that wanted to analyze how the subsystem in the candidate system processed. The system of the theory explained that system can be separated to each component to be analyzed as the independent entity and the component can be added as linear to picture the whole system. There were three general approaches to evaluate the subsystem. The holistic approach was to check the subsystem in a system. The functional approach to saw the top of the system to check the role in the bigger system. This study wanted to reveal the phenomenon of the political candidates in a system, how the elements of the subsystem were linear connected and influenced one to another, or not. Participant in mayor election was a couple of the candidates form a political party or the individual candidates that was recommended by a number of people. The public involvement that hardly seen, had to be from the local citizen that will be comped form political parties or individual candidates. This process was to determine the candidates of the mayor election of Kupang in 2017. The candidates should have the good and clean public institution management. This study reveals that each subsystem (input, process, and output) still had problems dan needed mending either the rules or procedures of the implication on every element that involved in the whole system. Individual candidates, from the beginning, had to be open about their intention so that the public did not refuse them. Verification procedures had to be simplified, the amount and the spreading of the supporter also had to be evaluated. This improvement had to be made by the rules which were the law. The process and procedure to determine the parties cadre in the public position had to be opened to the public and to the parties cadre. Keywords: transparency, candicate system processed, the mayor and vice election.